2019
DOI: 10.1021/jacs.8b11456
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Long-Range Order in Iridium Oxide by Alkali Ion for Efficient Water Oxidation

Abstract: Breaking long-range order in iridium oxide by alkali ion for efficient water oxidation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
364
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(389 citation statements)
references
References 60 publications
25
364
0
Order By: Relevance
“…In literatures, the Tafel slopes of crystalline IrO 2 and metallic Ir were recorded in the range from 40 to 70 and over 70 mV dec −1 , respectively, while the Tafel slopes for amorphous and hydrous IrO x were below 45 mV dec −1 in acidic media. [ 5,19 ] The Tafel slope of a ‐PN/IN frame/C was measured to be 47.49 mV dec −1 , indicating that the surface of a ‐PN‐IN frame/C consists of hydrous IrO x and crystalline IrO 2 as also revealed by XANES and XPS. Meanwhile, the Tafel slopes of a ‐PN‐IPN frame/C, a ‐IPN cage/C, and a ‐Ir/C catalysts were around 55 mV dec −1 , which are similar to the reported crystalline IrO 2 phases, indicating that these catalysts are less oxidized, leaving metallic Ir on the surface (Figure 4c,e).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In literatures, the Tafel slopes of crystalline IrO 2 and metallic Ir were recorded in the range from 40 to 70 and over 70 mV dec −1 , respectively, while the Tafel slopes for amorphous and hydrous IrO x were below 45 mV dec −1 in acidic media. [ 5,19 ] The Tafel slope of a ‐PN/IN frame/C was measured to be 47.49 mV dec −1 , indicating that the surface of a ‐PN‐IN frame/C consists of hydrous IrO x and crystalline IrO 2 as also revealed by XANES and XPS. Meanwhile, the Tafel slopes of a ‐PN‐IPN frame/C, a ‐IPN cage/C, and a ‐Ir/C catalysts were around 55 mV dec −1 , which are similar to the reported crystalline IrO 2 phases, indicating that these catalysts are less oxidized, leaving metallic Ir on the surface (Figure 4c,e).…”
Section: Resultsmentioning
confidence: 82%
“…[ 3 ] An amorphous form of electrochemically oxidized Ir (Ir III ) with the hydrated or hydroxylated structure has exhibited the highest catalytic activity among various material phases, owing to the flexible structure of catalytic sites. [ 4–6 ] Unfortunately, such Ir III oxides eventually worsen the OER performance because high potentials promote the oxidation and dissolution of active Ir during long‐term operation. [ 7–9 ] Meanwhile, Geiger et al showed that the rutile structure in IrO 2 (Ir IV ) exhibits much higher stability than amorphous Ir III oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Independently, the different researchers have found that under OER condition the surface of Ir-based catalysts finally forms short-range ordered octahedral IrO x H y phase ( Fig. 1) no matter what structure or composition of the catalysts started with [3][4][5]. This surface transfor-mation process is often called as surface reconstruction.…”
mentioning
confidence: 99%
“…Recently, many high‐performance and low‐cost catalysts, such as Co‐ and Ni‐based materials, have been developed for electrochemical and photoelectrocatalytic water oxidation in alkaline media. Nevertheless, OER in acidic environments is more imperative because of the high ionic (proton) conductivity and fewer side reactions of proton exchange membrane (PEM) electrolyzers . As reported, iridium oxide‐based nanocrystals are most widely used active and stable OER electrocatalysts in acidic electrolyte .…”
mentioning
confidence: 99%